123k views
4 votes
The work of a student to solve the equation 2(4x – 4) = 8 + 4x + 4 is shown below: Step 1. 2(4x – 4) = 8 + 4x + 4 Step 2. 6x – 6 = 12 + 4x Step 3. 6x – 4x = 12 + 6 Step 4. 2x = 18 Step 5. X = 9 In which step did the student first make an error and what is the correct step? Step 2,8x – 6 = 2(6 + 2x + 2) Step 2,8x – 8 = 12 + 4x Step 3,6x – 4x = 12 – 6 Step 3,6x + 4x = 12 + 6

2 Answers

2 votes

Answer:

Let's solve your equation step-by-step.

2(4x−4)=8+4x+4

Step 1: Simplify both sides of the equation.

2(4x−4)=8+4x+4

(2)(4x)+(2)(−4)=8+4x+4(Distribute)

8x+−8=8+4x+4

8x−8=(4x)+(8+4)(Combine Like Terms)

8x−8=4x+12

8x−8=4x+12

Step 2: Subtract 4x from both sides.

8x−8−4x=4x+12−4x

4x−8=12

Step 3: Add 8 to both sides.

4x−8+8=12+8

4x=20

Step 4: Divide both sides by 4.

4x

4

=

20

4

x=5

Answer:

x=5 is what they should've got so compare and you have your answer :D

User Zhiyong
by
5.2k points
5 votes

Answer:

1) The step 2 is wrong.

2) the correct step is 8x - 8 = 12 + 4x

Explanation:

2(4x – 4) = 8 + 4x + 4

Step 1. :

= 2(4x – 4) = 8 + 4x + 4

Step 2. :

=6x – 6 = 12 + 4x ( wrong)

This was wrong because , 2 multiplied by 4 is 8 not 6.

The correct way:

Step 1. :

2(4x – 4) = 8 + 4x + 4

Step 2. :


8x-8=12+4x

Step 3. :


8x-4x=12+8

Step 4. :


4x=20

Step 5. :


x=(20)/(4)=5

User Kesong Xie
by
5.9k points